The distribution of public equipments and its impact on the public service: case of the city of ammi Moussa, department of Relizane in Algeria - Hadji, Abdelkader; Feloussia, Lahcene (Technium Social Sciences Journal, 2022)
The city constitutes a center of human activity, and a base for a set of equipments and structures, which contribute in one way or another to the organization and creation of a population dynamic between it and surrounding centers and hence to the organization of the city itself. The needs and requirements of society vary from primary needs (education and health) to administrative, cultural and economic needs for an organized social life. Each category of needs is linked to social and economic norms, in particular the spatial characteristics, the scale of land consumption and the principles of sedentarization.This research aims to know the distribution of public equipments and its consistency with the demographic and urban growth of the city, and to show the quality of the public service of the facilities and its impact on the population, this is how the State strives to create equipment and distribute it in accordance with laws and decrees, including the theoretical equipment grid. The origin of the city of Ammi Moussa dates back to French colonialism, where it was founded as a prefecture in 1850, affiliated with the province of Oran, it is since 1984 that it has become the prefecture of the city by Relizane. The study included the different public facilities of the city, which were created and distributed under certain political, economic and social conditions, and in different periods. By comparing it with the theoretical standards of network equipment, it was found that they were incompatible, which led to an attack on the public service and the general organization of the city. , where it has experienced increasing population growth and difficulty in resisting the increasing pressure on the urban center, which contains most of the public amenities and facilities, which has caused a clear imbalance in its spatial organization. Therefore, the following question can be asked: how can the distribution of public facilities in the city play a role in the organization of its general urban space?